A comparative analysis of shunt active power filter and hybrid active power filter with different control techniques applied for harmonic elimination in a single phase system. (2015) - Puhan, Pratap Sekhar; Ray, Pravat Kumar; Panda, Gayadhar
This paper presents a comparative analysis between a single phase shunt active power filter (SPSAPF) and a single phase shunt hybrid filter (SPSHPF) to improve the power quality using different control techniques such as hysteresis current control and hysteresis fuzzy combined current control technique along with a different fuzzy rule (7/7 and 5/5) to a distribution system. An indirect current control technique along with hysteresis current control strategy is implemented on both the filters to generate the switching signal used for turning on and off of the insulated gate bipolar transistor. The indirect current control technique that is implemented for both filters is based on extracting the source current reference from the distorted waveform of the load current. The Simulink models are prepared. Simulation results are obtained and compared for both the filters with the same control technique, and it is observed that in every case SPSHPF shows excellent results in comparison to SPSAPF.